Pengaruh Pajak Daerah, Pertanian Kehutanan Dan Perikanan Terhadap PDRB di Kabupaten Kuningan Tahun 2012-2O22 - Faris, Muhammad; Apriliani, Nur Afni; Arifudin, Arifudin (FEB Universitas Sultan Ageng Tirtayasa, 2024)
GRDP is a reflection of the dynamics of a region's economy which is strongly influenced by the performance of economic sectors in the region. Local tax revenue is applied to finance the administration of local government and development for operational funds and development projects of a region. The agriculture, forestry and fisheries sector plays an important role in the regional economy in Indonesia, especially in regions whose economic base is based on the primary sector. However, this sector is still faced with the challenge of low productivity. Therefore, with the above statements and facts, the making of this journal is considered interesting to be applied with the SPSS method to test its influence, of course, to get concrete results from the test. After testing, the results obtained are the influence or very influential of local taxes, forestry agriculture and fisheries on GRDP in Kuningan Regency in 2012-2022.